“Impacto en la salud pública de la carne bovina contaminada por Salmonella” - Botto Barros, Betsy María (2023)
The objective of this bibliographic document was to study the impact of Salmonella contaminated beef on public health. It was developed by the inductive-deductive, documentary bibliographic method, in which the information obtained was paraphrased, summarized and analyzed. Salmonella is a bacterium that is distributed worldwide and affects humans and animals; to some extent, the Kauffmann-White protocol has defined 2600 serotypes and an enormous variety of hosts, which complicates the epidemiology of Salmonella. The serotypes of this pathogen are dangerous for humans and animals, according to its edition, this zoonosis is globally considered one of the fundamental problems in public health. Contaminated red meat consumed endangers public health by causing Salmonella salmonellosis. In animals destined for meat production, they can be the supply of infection in contaminated coolers and can generate contaminated waste, which can be used as raw material for different processes. Food handlers are the source of 30% of pathogenic microorganisms, including Salmonella, offering a serious risk to consumers. During slaughter, carcasses can become infected with these enteric pathogens related to fecal infection; desensitization technique, slaughter techniques, bleeding, evisceration and carcass treatment are directly related to beef safety. In public health, the consequences of Salmonella-infected meat for human consumption is the vital reason for numerous investigations, which forced to address some key factors within the origin and reproduction of Salmonella within the distribution system of meat for human consumption.